Critical Analysis of Strengthening Honest Character Through The Honesty Canteen at Kutabima 03 Cimanggu Elementary School Cimanggu District, Cilacap Regency Academic Year 2023/2024 - Indah Hapsari Arum Mawarni (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
This study aims to analyze the strengthening of honest character values through the honesty canteen at Kutabima 03 Cimanggu Elementary School. Methods and strategies have been implemented in efforts to strengthen honest character in the school environment, one of which is through the honesty canteen. The honesty canteen is a concept where the canteen is managed by relying on the honesty of its visitors. This study uses the Miles & Huberman data analysis technique. The subjects of this study are the principal, teachers, managers, and students. Data collection methods include interviews, observation, and documentation. Data verification techniques use source and technical triangulation. The results of the study indicate that the honesty canteen has great potential in instilling honesty values, but there are several supporting and inhibiting factors that need attention. Supporting factors include: support from the principal and teachers, involvement of students, parents, and the community, and effective socialization and education. On the other hand, inhibiting factors include a lack of implementation management, insufficient supervision, and evaluation of the honesty canteen implementation. The conclusion of this study is that the honesty canteen has a self-service system concept, which is a system where students carry out the purchase transaction process on their own without direct assistance from staff. Through this system, students are trained to act honestly when buying from the honesty canteen. The honesty canteen can be an effective learning medium for students in instilling honesty values